Trilogi Dakwah Rhoma Irama: Dakwah, Tablig, dan Politik: Rhoma Irama’s Preaching Trilogy: Preaching, Tablig, and Politics - Wahyudi AR, Nirwan (FAI UIM, 2024)
Music has the potential to become an instrument to invite listeners to do good as music also has the potential to become a means of inviting listeners to badness. Rhoma Irama as an artist, cultural observer, as well as a religious figure, realizes the strategic position of the art of music in da’wah. Rhoma's role as a da'i-musician has been going on for half a century with various romances and controversies, has become a separate treasure in the world of da'wah. It is a fact that is etched in history that Rhoma is one of the actors who advocate the da'wah movement through music, especially in the modern era. His legendary artworks are studied academically and non-academically both at home and abroad. However, it’s still difficult to trace the literature, especially the scientific literature that broadcasts about Rhoma's da'wah activities as da'i-preacher and da'i-politician. Whereas in fact, dangdut, tablig, and politics have become a trilogy or three in one in their da'wah struggle. This article is intended to describe and review Rhoma's trilogy descriptively by interactive qualitative research.